The use of creatine and its implications for physical activity practitioners (Research, Society and Development, 2024)
The present study aims to observe the effects of creatine on physical activity practitioners in different modalities with an emphasis on bodybuilding, through a narrative bibliographic review. Studies were carried out with various information taken mainly from scientific articles, found in journals such as SciElo PubMed, Ebsco, in addition to containing information from books and magazines focused on this area, we can analyze that creatine had several beneficial impacts both on the quality and intensity of training, and on the health of athletes, and showing no side effects, its use in a Controlled and the right dosages are not only beneficial, but also pose no danger to health.